(untitled) (Experimental biology, 2017)
Interaction sites of 784 intergenic miRNAs, 686 intronic miRNAs and 49 exonic miRNAs with mRNAs of 52 genes which are coded intronic miRNAs were studied. Feature interactions of miRNA with mRNA 5’UTR, CDS and 3’UTR of each gene are revealed. The raised affinity of miRNA sites to mRNA 5’UTRs in comparison with CDSs and 3’UTRs is established. mRNAs of 52 genes considerably differ on density of interaction sites and number of binding miRNAs. Various types of miRNAs interaction with mRNAs were revealed. They variously bring the contribution to interaction energy 5’- and 3’-parts miRNA were determined. Intronic miRNAs do not interact with mRNA of genes, which are coded by them. These data promotes understanding of the interaction mechanism miRNA and mRNA.